Understanding the changing television market: A comparison of the macroeconomy of the United States, United Kingdom and Australia. (February 2022) - Lotz, Amanda D.; Potter, Anna; Johnson, Catherine
The business of television has been transformed by digital distribution and internationalisation. The implications of these changes vary based on a range of structural dynamics such as national scale, language and pre-existing norms tied to particular macroeconomic conditions, of which, the balance of funding is key. This article looks beyond the general sense of crisis tied to digital disruption to investigate the macroeconomic conditions that shape how national television industries are able to adapt and respond to the disruption. Although disruption is universal, different macroeconomic conditions enable different industrial impacts and possible policy solutions. The article uses comparative analysis of three English language countries with very distinctive television ecologies to reveal the under-acknowledged role macroeconomic features – particularly the advent of new tools for advertising – play in shaping the options and opportunities for national industries going forward.